Advanced Computing and Systems for Security Volume 1 - Chaki, Rituparna; Cortesi, Agostino; Saeed, Khalid; Chaki, Nabendu; SpringerLink (Online service) (New Delhi : Springer India : Imprint: Springer, 2016)
The book contains the extended version of the works that have been presented and discussed in the Second International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2015) held during May 23-25, 2015 in Kolkata, India. The symposium has been jointly organized by the AGH University of Science & Technology, Cracow, Poland; Ca' Foscari University, Venice, Italy and University of Calcutta, India. The book is divided into volumes and presents dissertation works in the areas of Image Processing, Biometrics-based Authentication, Soft Computing, Data Mining, Next Generation Networking and Network Security, Remote Healthcare, Communications, Embedded Systems, Software Engineering and Service Engineering.
Security: Chapter 1. Computer User Profiling Based on Keystroke Analysis -- Chapter 2. Heart Based Biometrics and Possible Use of Heart Rate Variability in Biometric Recognition Systems -- Chapter 3. Dynamic Ciphering-15 Based on Multiplicative Polynomial Inverses over Galois Field GF(73) -- Chapter 4. On Preventing SQL Injection Attacks -- Chapter 5. Secure Data Retrieval Service in Remote Healthcare -- Systems Biology: Chapter 6. Inference of Gene Regulatory Networks with Neural-Cuckoo Hybrid -- Chapter 7. Detection of Diabetic Retinopathy Using the Wavelet Transform and Feed Forward Neural Network -- Chapter 8. Liver Fibrosis Diagnosis Support System Using Machine Learning Methods -- Chapter 9. Light-Weighted DNA Based Cryptographic Mechanism against Chosen Cipher Text Attacks -- Chapter 10. Genetic Algorithm Using Guide Tree in Mutation Operator for Solving Multiple Sequence Alignment -- Chapter 11. A Comparative Analysis of Image Segmentation Techniques Towards Automatic Risk Prediction of Solitary Pulmonary Nodules -- Networking and Cloud Computing: Chapter 12. SAFE-CLOUD: Secure and Usable Authentication FramEwork for CLOUD Environment -- Chapter 13. KPS: A Fermat Point Based Energy Efficient Data Aggregating Routing Protocol for Multi-sink Wireless Sensor Networks -- Chapter 14. The Design of Hierarchical Routing Protocol for  Wireless Sensor Network -- Chapter 15. Network Selection Using AHP for Fast Moving Vehicles in Heterogeneous Networks -- Chapter 16. Context-Aware Graph Based Visualized Clustering Approach (CAVCA) -- Chapter 17. Materialized View Construction Using Linearizable Non-Linear Regression.
Keywords: Computational intelligence; Signal processing; Data protection; Computational Intelligence; Signal, Speech and Image Processing; Data and Information Security